2021
DOI: 10.1177/0956462421997251
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sexually transmitted infection/HIV diagnosis among a predominantly university population in Brazil

Abstract: In Brazil, the increasing prevalence of HIV infection in young people makes it critical to know its distribution in university communities. In this cross-sectional study, we evaluated the impact of STI/HIV testing campaigns on university campuses from 2013 to 2017. The participants took part in rapid testing for HIV, syphilis, hepatitis B and C, and counseling sessions. A total of 2691 people participated in the campaigns. Of these, 79.4% were single, and 50.3% were women. The median age was 24 years old, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In relation to this, it has been reported that women with a low educational level have higher rates of sexual problems [ 72 , 73 , 74 ], specifically, poor orgasm experience [ 75 ]. This may be because low educational attainment is often associated with high levels of inappropriate sexual beliefs [ 76 ] and lower accessibility to quality sexual education, as most of these educational experiences occur in a formal academic context [ 77 ], which are essential to prevent infections and related difficulties [ 78 ]. The number of sexual partners also had a significant effect on the subjective experience of orgasm in comparisons by sex in the gay group and by sexual orientation, in men.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, it has been reported that women with a low educational level have higher rates of sexual problems [ 72 , 73 , 74 ], specifically, poor orgasm experience [ 75 ]. This may be because low educational attainment is often associated with high levels of inappropriate sexual beliefs [ 76 ] and lower accessibility to quality sexual education, as most of these educational experiences occur in a formal academic context [ 77 ], which are essential to prevent infections and related difficulties [ 78 ]. The number of sexual partners also had a significant effect on the subjective experience of orgasm in comparisons by sex in the gay group and by sexual orientation, in men.…”
Section: Discussionmentioning
confidence: 99%